Ultra-macroporous silica composite catalyst and preparation method thereof and method for preparing 2,2-dimethyl-1,3-dioxolane
By using ultra-large pore silica gel composite catalyst, the problems of catalysts being easily corroded, products not easily separated, and low selectivity in the prior art were solved, and the effect of efficient preparation of 2,2-dimethyl-1,3-dioxolane was achieved. The catalyst remained efficient after multiple use and had less environmental pollution.
Patent Information
- Application Number
- CN202111200910.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-14
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2041-10-14
AI Technical Summary
In the prior art, when preparing 2,2-dimethyl-1,3-dioxolane, the catalyst has the disadvantages of being susceptible to equipment, not being easy to separate products, and having low product selectivity.
Using an ultra-large pore silica gel composite catalyst, which consists of a support and silver nitrate supported on the support, a catalyst with excellent catalytic properties is prepared by a specific preparation method.
The catalyst exhibits a high conversion rate in the catalytic reaction, has high product purity, and the catalyst still maintains good catalytic performance after four repeated use, and has less environmental pollution.
Smart Images

Figure CN115970683B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst synthesis and application, and in particular to an ultra-macroporous silica composite catalyst and a preparation method thereof, and a method for preparing 2,2-dimethyl-1,3-dioxolane. Background Art
[0002] 2,2-Dimethyl-1,3-dioxolane is an important intermediate in the new process of ethylene glycol, a petrochemical product. The 1,3-dioxolane compound can be used as a solvent in industry to replace commonly used industrial solvents such as dichloromethane, dichloroethane and butanone, and can also be used as a solvent for polymers (Kirk-Othmer Encydopedia of Chemical Technology, John Wllley, Sons, Now Pork, Vol. 12: page 710).
[0003] In the prior art, when preparing 2,2-dimethyl-1,3-dioxolane, the catalyst used is an inorganic acid or an organic acid catalyst. When the acid catalyst catalyzes the cyclization reaction, it has the disadvantages of easy corrosion of the equipment, difficulty in separating the product, and low product selectivity.
[0004] Therefore, it is of great significance to study and develop a catalyst for preparing 2,2-dimethyl-1,3-dioxolane. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the catalyst used in the prior art in preparing 2,2-dimethyl-1,3-dioxolane, such as easy corrosion of equipment, difficulty in separating products and low product selectivity, and to provide an ultra-large pore silica gel composite catalyst and a preparation method thereof and a method for preparing 2,2-dimethyl-1,3-dioxolane. The catalyst has a high conversion rate when catalyzing the preparation of 2,2-dimethyl-1,3-dioxolane, and the catalyst still maintains good catalytic performance after being used repeatedly for four times.
[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides an ultra-macroporous silica composite catalyst, wherein the composite catalyst comprises a carrier and silver nitrate loaded on the carrier, wherein the carrier is an ultra-macroporous silica carrier, the carrier is a mesoporous sphere with a particle size of 30-60 μm, and the specific surface area of the carrier is 200-600 m 2 / g, the pore volume is 1.0-2.5 ml / g, and the pore size is bimodal distribution, wherein the first most probable pore size corresponding to the bimodal distribution is 5-10 nm and the second most probable pore size is 40-52 nm.
[0007] The second aspect of the present invention provides a method for preparing the aforementioned composite catalyst, characterized in that the preparation method comprises:
[0008] (1) mixing water glass, n-butanol, propylene glycol and an inorganic acid and contacting them, and filtering and / or washing the resulting mixture using a ceramic membrane filter to obtain a silica gel filter cake;
[0009] (2) ball-milling the silica gel filter cake obtained in step (1), and then spray-drying the mixture to obtain an ultra-large-porous silica gel carrier;
[0010] (3) The ultra-large pore silica gel carrier, acetone and silver nitrate are contacted for loading, and the loaded product is subjected to centrifugal separation, filtration and drying to obtain a composite catalyst.
[0011] The third aspect of the present invention provides a method for preparing 2,2-dimethyl-1,3-dioxolane, characterized in that the method comprises:
[0012] (1) contacting acetone and ethylene oxide in the presence of the composite catalyst to carry out a cyclization reaction;
[0013] (2) The obtained reaction product is centrifuged to obtain a liquid product 2,2-dimethyl-1,3-dioxolane.
[0014] Through the above technical scheme, the present invention adopts the super-large pore silica gel composite catalyst to carry out catalytic reaction, and the reactant has a high conversion rate, and almost no side reaction occurs during the reaction process, and the product purity is very high. In addition, the catalyst still maintains good catalytic performance after four repeated uses, and compared with the commonly used homogeneous catalyst, the catalyst has less environmental pollution. The present invention uses the super-large pore silica gel loaded with silver nitrate prepared by the present invention to catalyze the reaction of ethylene oxide and acetone. After the reaction, according to the gas chromatography analysis, the content of 2,2-dimethyl-1,3-dioxolane is as high as 60%, and the content of 2,2-dimethyl-1,3-dioxolane is as high as 55% after four times of recycling and reuse. After four catalytic reactions, the catalyst still maintains the ordered hexagonal pore structure unique to the mesoporous material.
[0015] After the reaction without adding any catalyst, the content of 2,2-dimethyl-1,3-dioxolane was only 3.6% according to gas chromatography analysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 is the XRD spectrum of the ultra-large pore silica gel carrier of the present invention;
[0017] Figure 2 This is a SEM scanning electron microscope image of the ultra-large pore silica gel carrier of the present invention;
[0018] Figure 3 It is a pore size distribution curve diagram of the ultra-large pore silica gel carrier of the present invention. DETAILED DESCRIPTION
[0019] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0020] The first aspect of the present invention provides an ultra-macroporous silica composite catalyst, wherein the composite catalyst comprises a carrier and silver nitrate loaded on the carrier, wherein the carrier is an ultra-macroporous silica carrier, the carrier is a mesoporous sphere with a particle size of 30-60 μm, and the specific surface area of the carrier is 200-600 m 2 / g, the pore volume is 1.0-2.5 ml / g, and the pore size is bimodal distribution, wherein the first most probable pore size corresponding to the bimodal distribution is 5-10 nm and the second most probable pore size is 40-52 nm.
[0021] The inventor of the present invention unexpectedly discovered that the present invention first utilizes the ball milling method to synthesize ultra-large porous silica gel loaded with silver nitrate. The mesoporous material synthesized by this method is a new type of superacid catalytic material, which shows excellent catalytic performance in the catalytic reaction. The catalyst is used to catalyze ethylene oxide and acetone to obtain 2,2-dimethyl-1,3-dioxolane, which is important in industry.
[0022] According to the present invention, the specific surface area of the carrier is 300-500m 2 / g, the pore volume is 1.3-1.8ml / g, the pore size is bimodal, the first most probable pore size corresponding to the bimodal is 6-9nm and the second most probable pore size is 43-50nm; in the present invention, the carrier is limited to the aforementioned range, which can give full play to the structural advantages of the carrier and make the loading of the active component more uniform.
[0023] According to the present invention, based on the total weight of the composite catalyst, the content of the carrier is 70-92 weight%, and the content of the silver nitrate is 8-30 weight; preferably, based on the total weight of the composite catalyst, the content of the carrier is 80-88 weight%, and the content of the silver nitrate is 12-20 weight. In the present invention, the content of the carrier and the silver nitrate is limited to the above range, so that the silver nitrate can be evenly dispersed on the surface of the carrier, and can play the maximum effect in the cyclization reaction process.
[0024] According to the present invention, the specific surface area of the catalyst is 150-450m 2 / g, pore volume of 0.8-1.8ml / g, pore size of bimodal distribution, the first most probable pore size corresponding to the bimodal distribution is 4-8nm and the second most probable pore size is 30-48nm; preferably, the specific surface area of the catalyst is 200-400m 2 / g, pore volume is 0.9-1.5ml / g, pore size is bimodal, the first most probable pore size corresponding to the bimodal is 5-7nm and the second most probable pore size is 35-42nm. In the present invention, the parameters of the catalyst are limited to the aforementioned range, which has the advantage that the catalyst structure is most conducive to the cyclization reaction and can effectively improve the yield of the target product.
[0025] The second aspect of the present invention provides a method for preparing the aforementioned composite catalyst, characterized in that the preparation method comprises:
[0026] (1) mixing water glass, n-butanol, propylene glycol and an inorganic acid and contacting them, and filtering and / or washing the resulting mixture using a ceramic membrane filter to obtain a silica gel filter cake;
[0027] (2) ball-milling the silica gel filter cake obtained in step (1), and then spray-drying the mixture to obtain an ultra-large-porous silica gel carrier;
[0028] (3) The ultra-large pore silica gel carrier, acetone and silver nitrate are contacted for loading, and the loaded product is subjected to centrifugal separation, filtration and drying to obtain a composite catalyst.
[0029] According to the present invention, the weight ratio of the water glass, the inorganic acid, n-butanol and glycerol is 1: (0.05-0.5): (0.02-0.6): (0.02-0.6); preferably, the weight ratio of the water glass, the inorganic acid, n-butanol and glycerol is 1: (0.1-0.3): (0.06-0.4): (0.06-0.4).
[0030] According to the present invention, in step (1), the water glass, the inorganic acid, n-butanol and glycerol are mixed and contacted to react at a temperature of 15-80° C. for 0.5-20 h; preferably, the temperature is 25-50° C. and the time is 1-6 h.
[0031] According to the present invention, after the mixed contact reaction, 98 wt % sulfuric acid is used to adjust the pH value, wherein the pH value is 1.5-4.5, preferably, the pH value is 2-4; and then the obtained reaction material is filtered.
[0032] According to the present invention, the prepared silica gel filter cake is put into a ball mill for ball milling, wherein the ball mill is made of polytetrafluoroethylene, the grinding ball is made of agate, the diameter of the grinding ball is 3 mm, the number is 1, and the rotation speed is 400 r / min. The ball mill is closed and the temperature in the ball mill is 30-80° C. for 2-20 hours.
[0033] According to the present invention, the spray drying conditions may include: a temperature of 100-300°C, and a rotation speed of 10000-15000 r / min; preferably, the spray drying conditions include: a temperature of 150-250°C, and a rotation speed of 11000-13000 r / min.
[0034] According to the present invention, the ultra-macroporous silica gel carrier is dried in advance under vacuum conditions, wherein the drying conditions include: a temperature of 110-160° C. and a drying time of 4-10 hours.
[0035] According to the present invention, in step (3), the loading conditions include: temperature of 20-80°C, time of 1-20h; preferably, temperature of 40-60°C, time of 3-10h. In the present invention, the reaction is carried out in a closed polytetrafluoroethylene-lined reactor.
[0036] According to the present invention, in step (3), the filtering and washing conditions are not particularly limited. For example, the filtering and washing process may include: obtaining a solid product after filtering, repeatedly washing the solid product with distilled water (the number of washing times may be 2-10) and then filtering with suction.
[0037] According to the present invention, in step (3), the drying conditions include: temperature of 100-150° C. and time of 3-20 h.
[0038] The third aspect of the present invention provides a method for preparing 2,2-dimethyl-1,3-dioxolane, wherein the method comprises:
[0039] (1) contacting acetone and ethylene oxide in the presence of the composite catalyst to carry out a cyclization reaction;
[0040] (2) The obtained reaction product is centrifuged to obtain a liquid product 2,2-dimethyl-1,3-dioxolane.
[0041] According to the present invention, the mass ratio of the ethylene oxide, the acetone and the catalyst is 1:(1-10):(0.01-0.3); preferably 1:(2-5):(0.1-0.3).
[0042] According to the present invention, in step (1), the conditions of the cyclization reaction include: temperature of 50-100°C, time of 1-72h; preferably, temperature of 60-90°C, time of 3-20h.
[0043] According to the present invention, the method further comprises: drying the solid phase product obtained by centrifugal separation to obtain a recovered catalyst; wherein the drying conditions comprise: a temperature of 25-200°C and a time of 1-24h; preferably, a temperature of 60-160°C and a time of 2-10h.
[0044] According to a particularly preferred embodiment of the present invention, a method for preparing 2,2-dimethyl-1,3-dioxolane comprises:
[0045] Step 1: Add ethylene oxide and acetone into the reactor, and add ultra-large porous silica gel loaded with silver nitrate as a catalyst, according to the mass feed ratio.
[0046] Ethylene oxide: acetone: catalyst = 1: (1-10): (0.01-0.3),
[0047] Step 2, stirring the reaction under heating conditions for 0.1-72 hours, cooling to room temperature, and centrifuging for solid-liquid separation;
[0048] Step 3: distill and separate the obtained liquid phase product to obtain the product 2,2-dimethyl-1,3-dioxolane. The distillation separation adopts conventional known technology.
[0049] The solid phase product obtained by centrifugal separation in step 2 is vacuum dried at 25-200° C. for 1-24 hours to obtain a recovered catalyst.
[0050] The present invention will be described in detail below through examples.
[0051] It is calculated based on the results of gas chromatography-mass spectrometry analysis. During the calculation process, the specific determination of each substance is given by comparing the given mass spectrum with the standard spectrum input into the computer.
[0052] The XRD spectra of the samples were obtained on an X'Pert MPD X-ray powder diffractometer produced by Philips, using CuKα radiation, λ=0.154178nm, and a scanning range of 2θ=0.5° to 10°;
[0053] The pore structure parameter analysis of the samples was carried out on an ASAP2020-M+C adsorption instrument purchased from Micromeritics, USA;
[0054] The specific surface area of the samples was calculated using the BET method, and the pore volume was calculated using the BJH model;
[0055] The SEM images of the samples were obtained on an XL-30 field emission environmental SEM produced by FEI Company of the United States;
[0056] The elemental analysis experiment of the catalyst samples was carried out on an EagleⅢ energy dispersive X-ray fluorescence spectrometer produced by EDAX Company in the United States;
[0057] The drying oven was produced by Shanghai Yiheng Scientific Instrument Co., Ltd., model DHG-9030A.
[0058] The reagents used in the examples and comparative examples were purchased from Sinopharm Chemical Reagent Co., Ltd. and were of analytical purity.
[0059] Example 1
[0060] This example is intended to illustrate the preparation of a super-macroporous silica gel composite catalyst loaded with silver nitrate.
[0061] (1) Preparation of ultra-large-porous silica carrier:
[0062] In the first step, 15 wt% water glass, 12 wt% sulfuric acid solution, n-butanol and propylene glycol are mixed in a weight ratio of 1:0.2:0.2:0.2 and contacted at 20°C for 1.5 hours, followed by adjusting the pH value to 3 with 98 wt% sulfuric acid, and then filtering the obtained reaction materials and washing them with distilled water on a ceramic membrane filter until the sodium ion content is 0.02 wt% to obtain a silica gel filter cake, and three tons of washing water are used for one ton of silica gel filter cake.
[0063] 10g of the silica gel filter cake prepared above was put into a 100mL ball mill, wherein the ball mill was made of polytetrafluoroethylene, the grinding ball was made of agate, the diameter of the grinding ball was 3mm, the number was 1, and the rotation speed was 400r / min. The ball mill was sealed and ball milled for 5h at a temperature of 60°C in the ball mill to obtain a slurry; the slurry was spray dried at 200°C and a rotation speed of 12000r / min to obtain the target carrier.
[0064] Figure 1 is the XRD spectrum of the ultra-large pore silica gel carrier according to the present invention. Figure 1 It can be seen that the ultra-large porous silica gel carrier has a two-dimensional hexagonal pore structure.
[0065] Figure 2 : is a SEM scanning electron microscope image of the super-large pore silica gel carrier according to the present invention. Figure 2 It can be seen that the microscopic morphology of the ultra-macroporous silica gel A is spherical particles with an average particle size of 30-60 μm.
[0066] Figure 3TABLE 1 is the average pore size distribution diagram of the ultra-large pore silica gel carrier according to the present invention. The pore size of the material is bimodal, with the first most probable pore size being 7.8 nm and the second most probable pore size being 43 nm. The pore structure parameters of the ultra-large pore silica gel carrier are listed in Table 1.
[0067] (2) Preparation of composite catalyst:
[0068] Step 2: vacuum dry 1g of the mesoporous material at 150°C for 6 hours, cool to room temperature, then put 15ml of acetone and 1g of silver nitrate into a 100ml polytetrafluoroethylene-lined reactor, seal the reactor, and stir at 55°C for 24 hours.
[0069] Step 3, after cooling to room temperature, the liquid was filtered by centrifugation to obtain a solid product, which was vacuum dried at 150°C for 4 hours to remove impurities and obtain a product, whose structural parameters are shown in Table 1.
[0070] In addition, based on the total weight of the composite catalyst, the content of the carrier was 84 weight percent, and the content of the silver nitrate was 16 weight percent.
[0071] Table 1
[0072]
[0073] Example 2
[0074] This example is to illustrate the use of the catalyst prepared in Example 1 to prepare 2,2-dimethyl-1,3-dioxolane.
[0075] Weigh 1 gram of the silver nitrate-loaded ultra-large porous silica gel composite catalyst prepared in Example 1, and then weigh 11.6 grams of acetone and 4.4 grams of ethylene oxide, and put them into a 100 ml polytetrafluoroethylene-lined reactor in sequence, and stir them at 75° C. for 4 hours. After cooling to room temperature, centrifuge and analyze the reaction product liquid components by gas chromatography. The reaction product liquid components were analyzed by gas chromatography, and the 2,2-dimethyl-1,3-dioxolane content was 60%.
[0076] The solid catalyst mesoporous material was vacuum dried at 150°C for 6 hours, cooled to room temperature, and then recovered and reused, which was marked as S1-Recovery 1.
[0077] Example 3
[0078] This example is to illustrate the preparation of 2,2-dimethyl-1,3-dioxolane using the catalyst recovered once in Example 2.
[0079] 1 gram of the mesoporous material catalyst S1-Recovery 1 recycled from Example 2, 11.6 grams of acetone and 4.4 grams of ethylene oxide were weighed and put into a 100 ml polytetrafluoroethylene-lined reactor in sequence, and stirred at 75°C for 4 hours. After cooling to room temperature, the mixture was centrifuged and the reaction product liquid composition was analyzed by gas chromatography. The content of 2,2-dimethyl-1,3-dioxolane was 58%.
[0080] The solid catalyst mesoporous material was vacuum dried at 150°C for 6 hours, cooled to room temperature, and then recovered and reused, which was marked as S1-Recovery 2.
[0081] Example 4
[0082] This example is to illustrate the preparation of 2,2-dimethyl-1,3-dioxolane using the catalyst recovered for the second time in Example 3.
[0083] 1 gram of the mesoporous catalyst S1-2 recycled from Example 3 was recycled, and 11.6 grams of acetone and 4.4 grams of ethylene oxide were weighed and put into a 100 ml polytetrafluoroethylene-lined reactor in sequence, and stirred at 75°C for 4 hours. After cooling to room temperature, the mixture was centrifuged and the reaction product liquid composition was analyzed by gas chromatography, and the content of 2,2-dimethyl-1,3-dioxolane was 57%.
[0084] The solid catalyst mesoporous material was vacuum dried at 150°C for 6 hours, cooled to room temperature, and then recovered and reused, which was marked as S1-recovery 3.
[0085] Example 5
[0086] This example is to illustrate the preparation of 2,2-dimethyl-1,3-dioxolane using the catalyst recovered three times in Example 4.
[0087] 1 gram of the mesoporous material catalyst S1-3 recycled from Example 4 was recycled, and 11.6 grams of acetone and 4.4 grams of ethylene oxide were weighed and put into a 100 ml polytetrafluoroethylene-lined reactor in sequence, and stirred at 75°C for 4 hours. After cooling to room temperature, the mixture was centrifuged and the reaction product liquid composition was analyzed by gas chromatography, and the content of 2,2-dimethyl-1,3-dioxolane was 56%.
[0088] The solid catalyst mesoporous material was vacuum dried at 150°C for 6 hours, cooled to room temperature, and then recovered and reused, which was marked as S1-recovery 4.
[0089] Example 6
[0090] This example is to illustrate the preparation of 2,2-dimethyl-1,3-dioxolane using the catalyst recovered three times in Example 5.
[0091] 1 gram of the mesoporous material catalyst S1-Recovery 4 recycled from Example 5, 11.6 grams of acetone and 4.4 grams of ethylene oxide were weighed and put into a 100 ml polytetrafluoroethylene-lined reactor in sequence, and stirred at 75°C for 4 hours. After cooling to room temperature, the mixture was centrifuged and the reaction product liquid composition was analyzed by gas chromatography. The content of 2,2-dimethyl-1,3-dioxolane was 55%.
[0092] Comparative Example 1
[0093] 11.6 g of acetone and 4.4 g of ethylene oxide were weighed and placed in a 100 ml polytetrafluoroethylene-lined reactor in sequence. The mixture was stirred at 75° C. for 4 hours. After cooling to room temperature, the mixture was centrifuged and the composition of the reaction product liquid was analyzed by gas chromatography. The content of 2,2-dimethyl-1,3-dioxolane was 3.6%.
[0094] Comparative Example 2
[0095] 2,2-dimethyl-1,3-dioxolane was prepared in the same manner as in Example 2, except that the "ultra-macroporous silica gel composite catalyst loaded with silver nitrate prepared in Example 1" was replaced by a "conventional mesoporous catalyst having a specific surface area of 267 m 2 / g, pore volume 0.3cm 3 / g, and the average pore size is 5nm".
[0096] As a result, the 2,2-dimethyl-1,3-dioxolane content was 41%.
[0097] Comparative Example 3
[0098] 2,2-dimethyl-1,3-dioxolane was prepared in the same manner as in Example 2, except that the "ultra-large pore silica gel composite catalyst loaded with silver nitrate prepared in Example 1" was replaced with "ultra-large pore silica gel composite catalyst loaded with zinc nitrate, which is loaded with zinc nitrate instead of silver nitrate.".
[0099] As a result, the 2,2-dimethyl-1,3-dioxolane content was 32%.
[0100] Comparative Example 4
[0101] 2,2-dimethyl-1,3-dioxolane was prepared in the same manner as in Example 2, except that the "ultra-large pore silica gel composite catalyst loaded with silver nitrate prepared in Example 1" was replaced with "ultra-large pore silica gel composite catalyst D loaded with silver nitrate, and based on the total weight of the composite catalyst D, the content of the carrier was 96 weight%, and the content of the silver nitrate was 4 weight".
[0102] As a result, the 2,2-dimethyl-1,3-dioxolane content was 37%.
[0103] The experimental results show that the ultra-macroporous silica composite catalyst loaded with silver nitrate prepared by the method of the present invention has a significantly better effect in the synthesis reaction of 2,2-dimethyl-1,3-dioxolane. Compared with conventional catalysts, the catalyst provided by the present invention can reduce side reactions and obtain more target products.
[0104] Since the catalyst of the present invention was not used in Comparative Example 1, no product was generated and the amount of product generated was very low.
[0105] Since the conventional mesoporous catalyst with a single-channel structure was used in Comparative Example 2, the active components were unevenly distributed and the amount of target product generated was low.
[0106] In Comparative Example 3, the catalyst does not carry silver nitrate, but carries zinc nitrate as the active component. Since the catalytic activity of zinc nitrate is lower than that of silver nitrate of the same weight, the amount of target product generated is lower.
[0107] In Comparative Example 4, the content of the carrier in the catalyst is too high, and the content of the active component silver nitrate is too low. Due to the insufficient active components in the reaction, the amount of the target product generated is low.
[0108] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A super-macroporous silica composite catalyst, characterized in that: The composite catalyst comprises a carrier and silver nitrate loaded on the carrier, wherein the carrier is an ultra-macroporous silica gel carrier, the carrier is a mesoporous sphere with a particle size of 30-60 μm, and the specific surface area of the carrier is 200-600 m 2 / g, the pore volume is 1-2.5 ml / g, and the pore size is bimodal distribution. The first most probable pore size corresponding to the bimodal distribution is 5-10 nm and the second most probable pore size is 40-52 nm.
2. The composite catalyst according to claim 1, wherein The specific surface area of the carrier is 300-500m 2 / g, the pore volume is 1.3-1.8 ml / g, and the pore size is bimodal distribution. The first most probable pore size corresponding to the bimodal distribution is 6-9 nm and the second most probable pore size is 43-50 nm.
3. The composite catalyst according to claim 1, wherein Based on the total weight of the composite catalyst, the content of the carrier is 70-92% by weight, and the content of the silver nitrate is 8-30% by weight.
4. The composite catalyst according to claim 3, wherein Based on the total weight of the composite catalyst, the content of the carrier is 80-88% by weight, and the content of the silver nitrate is 12-20% by weight.
5. The composite catalyst according to any one of claims 1 to 4, wherein The specific surface area of the catalyst is 150-450m 2 / g, the pore volume is 0.8-1.8 ml / g, and the pore size is bimodal distribution. The first most probable pore size corresponding to the bimodal distribution is 4-8 nm and the second most probable pore size is 30-48 nm.
6. A method for preparing the composite catalyst according to any one of claims 1 to 5, characterized in that: The preparation method comprises: (1) mixing water glass, n-butanol, propylene glycol and an inorganic acid and contacting them, and filtering and / or washing the resulting mixture using a ceramic membrane filter to obtain a silica gel filter cake; (2) ball-milling the silica gel filter cake obtained in step (1), and then spray-drying it to obtain an ultra-large-porous silica gel carrier; (3) The ultra-large pore silica gel carrier, acetone and silver nitrate are contacted for loading, and the loaded product is subjected to centrifugal separation, filtration and drying to obtain a composite catalyst.
7. The preparation method according to claim 6, wherein: The weight ratio of the water glass, the inorganic acid, n-butanol and glycerol is 1: (0.05-0.5): (0.02-0.6): (0.02-0.6); And / or, in step (1), the mixed contact conditions include: temperature of 15-80°C, time of 0.5-20h; And / or, in step (3), the conditions of the loading reaction include: temperature of 20-80° C. and time of 1-20 h.
8. A method for preparing 2,2-dimethyl-1,3-dioxolane, characterized in that: The method includes: (1) contacting acetone and ethylene oxide in the presence of the composite catalyst according to any one of claims 1 to 5 to carry out a cyclization reaction; (2) The obtained reaction product is centrifuged to obtain a liquid product 2,2-dimethyl-1,3-dioxolane.
9. The method according to claim 8, wherein: The mass ratio of the ethylene oxide, the acetone and the catalyst is 1:(1-10):(0.01-0.3); And / or, in step (1), the conditions of the cyclization reaction include: temperature of 50-100° C. and time of 1-72 h.
10. The method according to claim 8, wherein: The method further comprises: drying the solid phase product obtained by centrifugal separation to obtain a recovered catalyst.
11. The method according to claim 10, wherein: The drying conditions include: temperature of 25-200° C. and time of 1-24 h.
Citation Information
Patent Citations
Mesoporous composite material and catalyst, preparation method and application thereof, and preparation method of 2,2-dimethyl-4-methyl-1,3-dioxolane
CN105214735A
Alumina carrier, preparation method and silver catalyst
CN105435792A